The influence of mergers on the cluster temperature function and cosmological parameters derived from it - Angrick, Christian; Bartelmann, Matthias (Arxiv, 2017)
We develop a parameter-free analytic model to include the effects of mergers into the theoretical modelling of the X-ray temperature function of galaxy clusters. We include this description into our model for the cluster population based on fluctuations of the gravitational potential, which avoids any reference to mass. Comparisons with a numerical simulation reveal that the theoretical model is in good agreement with the simulation results. We show that building the model on the dynamics of spherical rather than ellipsoidal collapse yields better results if emission-weighted temperatures are used, while ellipsoidal collapse yields good agreement between model and simulation for mass-weighted temperatures. Analysing two different samples of X-ray clusters, we quantify the influence of mergers and a conversion between different temperature definitions on the joint determination of Omega_m0 and sigma_8. If effects of mergers are included, temperature functions based on cluster masses and on the gravitational potential built on spherical collapse are in good agreement with other cosmological probes without any conversion of temperatures.
Gesehen am 22.09.2017